Correlation Between Pleural Fluid GenXpert® and Histopathology Finding of Pleural Biopsy in Tuberculous Pleural Effusion - Sheilla Matheos; Isnin Anang Marhana; Anny Setijo Rahaju (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2018)
Backgrounds: Tuberculosis pleural effusion is the most common extrapulmonary TB after lymphadenitis TB, but a definite diagnosis is still a challenge. Pleural biopsy has historically been the gold standard procedure for the diagnosis of pleural tuberculosis. GenXpert® is a computerize test based in nucleic acid amplification tahat automatically detect MTB and rifampicin resistance. This study aimed to prove the correlation between pleural fluid GenXpert® and histopathological findings of pleural biopsy in patients with pleural tuberculosis. Methods: This study used an observational analytic design with a cross-sectional design conducted in Dr. Soetomo Hospital, Surabaya in March-June 2017. Statistic analysis was using chi square test and contingensi coofisient. The pleural GenXpert® was tested in 23 patients with pleural effusion and their biopsy speciments underwent histopathological analysis. Results: Histopathological findings of pleural biopsy was positive in 4 subjects and pleural fluid GenXpert® resulted positive in 6 subjects. There was significant correlation between pleural fluid GenXpert® and histopathological findings of specimen pleural biopsy in patients with pleural tuberculosis (P=0.040) with moderate strenght (P=0.014). Sensitivity and specificity of pleural fluid GenXpert® were 75.0% dan 84.2% respectively. Conclusions: There was significant correlation between pleural fluid GenXpert® and histopathological findings of pleural biopsy in patients with pleural tuberculosis. (J Respir Indo 2018; 38(1): 1-6)